NEGOSIASI IDENTITAS TRANSGENDER (Studi pada Komunitas Transgender PERWAJO Kota Jombang) - Hapsari, Alfaridza Ainun; Suryandari, Nikmah (Interaksi: Jurnal Ilmu Komunikasi, 2023)
Transgender identity is still a pro and con for some people in Indonesia, especially in areas with high culture and religiosity. Transgender people are considered not to heed the norms prevailing in the environment. This study aims to analyze the identity negotiations of members of the transgender community in the city of Jombang Persatuan Waria Jombang (PERWAJO). The theories and concepts used in this study are identity negotiations, and transgender. This research uses qualitative descriptive research methods, as well as phenomenological approaches. The results of the study showed: Efforts to open up transgender members of the Jombang Waria Association (PERWAJO). PERWAJO members made an early opening by constructing appearance and behavior to be feminine. In addition, PERWAJO members also participate in various types of communities in their environment; PERWAJO became the medium for opening up transgender identity. Obstacles in opening up identity come from society, family, and environment.